2012
DOI: 10.1080/02755947.2012.685140
|View full text |Cite
|
Sign up to set email alerts
|

Defining Economic Injury Levels for Sea Lamprey Control in the Great Lakes Basin

Abstract: We estimated economic injury levels (EILs) and associated optimal control budgets for sea lamprey Petromyzon marinus for each of the Great Lakes using common assumptions and consistent methods. The lake‐specific EILs are defined as equilibrium sea lamprey abundances below which incremental increases in control expenditures do not pay for themselves in terms of benefits (in the form of increased harvest of desired host species). We assume that sea lamprey control efforts result in an increase in the availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…Actual larval survival rates are highly uncertain, but some estimates are available. These estimates are somewhat higher than the values (39.5-51.8 %) used in sea lamprey population model simulations Irwin et al 2012), but are generally lower than those (52-96 %) reported by from cage studies in which predators would have been excluded. Weise and Pajos (1998) estimated annual survival of one age class of sea lamprey larvae to be 61 % (see below).…”
Section: Mortality Factors In Different Life Stagescontrasting
confidence: 54%
“…Actual larval survival rates are highly uncertain, but some estimates are available. These estimates are somewhat higher than the values (39.5-51.8 %) used in sea lamprey population model simulations Irwin et al 2012), but are generally lower than those (52-96 %) reported by from cage studies in which predators would have been excluded. Weise and Pajos (1998) estimated annual survival of one age class of sea lamprey larvae to be 61 % (see below).…”
Section: Mortality Factors In Different Life Stagescontrasting
confidence: 54%
“…First, we calibrated the model for each Great Lake by adjusting larval natural mortality rates such that recent observed adult sea lamprey abundance levels were forecasted, on average, when recent levels of lampricide control were applied (c.f. Irwin et al 2012). Second, we ran simulations for each lake with no lampricide control applied, to estimate population abundances associated with no control.…”
Section: R a F Tmentioning
confidence: 99%
“…The model includes uncertainty in biological processes (recruitment and growth), assessment of larval abundance in reaches considered for treatment, and implementation of lampricide control. This model was successfully applied to evaluate allocation of budgetary resources between larval population assessment and other management actions ), conduct a preliminary assessment of integrated control strategies (i.e., lampricide and alternative control [specifically adult-targeted alternative control]; Dawson [2007]), and generate estimates of economic injury levels (Szlai et al [2005], Irwin et al [2012]).…”
Section: Model Overviewmentioning
confidence: 99%